Small-Scale Heterogeneity in Drinking Water Biofilms - Neu, Lisa; Proctor, Caitlin R.; Walser, Jean-Claude; Hammes, Frederik (Frontiers in Microbiology, 2019)
Biofilm heterogeneity has been characterized on various scales for both natural and engineered ecosystems. This heterogeneity has been attributed to spatial differences in environmental factors. Understanding their impact on localized biofilm heterogeneity in building plumbing systems is important for both management and representative sampling strategies. We assessed heterogeneity within the confined engineered ecosystem of a shower hose by high-resolution sampling (200 individual biofilm sections per hose) on varying scales (µm to m). We postulated that a biofilm grown on a single material under uniform conditions should be homogeneous in its structure, bacterial numbers, and community composition. A biofilm grown for 12 months under controlled laboratory conditions, showed homogeneity on large-scale. However, some small-scale heterogeneity was clearly observed. For example, biofilm thickness of cm-sections varied up to 4-fold, total cell concentrations (TCC) 3-fold, and relative abundance of dominant taxa up to 5-fold. A biofilm grown under real (i.e., uncontrolled) use conditions developed considerably more heterogeneity in all variables which was attributed to more discontinuity in environmental conditions. Interestingly, biofilm communities from both hoses showed comparably low diversity, with < 400 taxa each, and only 3 taxa accounting for 57 % respectively 73 % of the community. This low diversity was attributed to a strong selective pressure, originating in migrating carbon from the flexible hoses as major carbon source. High-resolution sampling strategy enabled detailed analysis of spatial heterogeneity within an individual drinking water biofilm. This study gives insight into biofilm structure and community composition on cm-to m-scale and is useful for decision-making on sampling strategies in biofilm research and monitoring.